Epidemiology and Control of Peste des Petits Ruminants (ECo-PPR) Study Design and Toolbox (version 2) - CGIAR Research Program on Livestock (2021)
Tool has been used by local partners in six countries in East and West Africa (Senegal, Mali, Burkina Faso, Kenya, Ethiopia and Tanzania) to collect data on socio-economic impact of PPR across different production systems (https://hdl.handle.net/10568/116575)